Exploring the Use of Intelligent Agents for Team Training - Mountjoy, Daniel N; Russell, Janeria D; Ram, Bala; Yu, Xuefeng (International Journal of Industrial Engineering: Theory, Applications and Practice, 2022)
Teams within or across organizations are becoming more widely distributed in terms of their geographical location. This can result in expensive training sessions that are difficult to schedule. Therefore, tools used to train distributed team members should be designed so the knowledge, skills, and behavior of others can be learned through the assistance of remote training modules. The use of intelligent agents is becoming more popular because of its ability to simulate work related situations autonomously and flexibly. This work was performed to determine if an intelligent agent-based software tool can be used to effectively train geographically distributed teams. Five types of training were administered and compared to examine team performance, as well as individual knowledge and skills acquired during a simple manufacturing supply chain scenario. Results indicate the agent-based training has a positive training effect and can be used as an effective method of team training.